Evidence of the relative age effect in youth soccer players from Turkey - Köklü, Y.; Arslan, Y.; Alemdaroglu, U. (Kinesiologia Slovenica, 2017)
The main purpose of this study was to ascertain whether the relative age effect (RAE) exists in development teams of soccer clubs across different professional leagues in Turkey. The players were allocated to one of six age subgroups (U14, U15, U16, U17, U19, U21) and league level was also considered as a factor; data on 8600 players in 408 professional teams were analyzed. Birth data and registration dates were collected by accessing the Turkish Football Federation`s official website. The results showed that the RAE is strong and significant for each lower league and per age category (p 0.05). An independent samples t-test on U21 soccer players` TE means also yielded no significant difference (p> 0.05). In conclusion, amongst soccer players in development teams of professional clubs in Turkey, players born in the later months of the year are less likely to be selected than those born in the earlier months. It is also concluded that there is no association between TE and a player`s league level.